TREATMENT OF CONJUNCTIVITIS IN PUMA CUBS IN LAHORE ZOO, PAKISTAN - S. Shahzad; M.B. Saleem; A. K. Mahmood; S.Y. Shelly; S. S. Ahmad; Z. Tariq; Z. Qadir Lahore Zoo Lahore; Pakistan (Journal of Animal and Plant Sciences, 2015)
Conjunctivitis is an inflammation of the conjunctiva, often called pink eye and is common in young felids wild, captive or domestic. Two, 2½ months old puma cubs were reported with conjunctivitis at Lahore Zoo. They appeared dull and sluggish with protruded third eyelids along with ocular discharge and slight corneal opacity in both eyes. The cubs were treated with antibiotics and supplemented with vitamin A. Cubs responded the treatment within three days and recovered completely in four weeks. 2011) topical ophthalmic application of cidofovir
Keywords: conjunctivitis; puma cub; felids; Lahore zoo.